Method for preparing metal-nitrogen co-doped carbon material by using waste artificial boards and application of metal-nitrogen co-doped carbon material

By coordinating the waste artificial plate with metal units, metal-nitrogen co-doped carbon materials were prepared, which solved the problems of easy precipitation of metal ions and uneven distribution of catalytic sites in the prior art, and achieved efficient adsorption and catalytic effects of organic pollutants in water bodies.

CN119524801APending Publication Date: 2025-02-28INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411705092.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when using waste artificial boards to prepare carbon materials, metal ions are prone to precipitation and uneven distribution of catalytic sites, resulting in poor catalytic performance.

Method used

By coordinating the waste artificial plate with metal units, activated and carbonized at high temperature, metal-nitrogen co-doped carbon material was prepared, which solved the problem of uneven distribution of metal ions.

Benefits of technology

The effective preparation of metal-nitrogen co-doped carbon materials is achieved, and its performance in adsorption and catalytic degradation of organic pollutants in water bodies is improved. It has the advantages of being efficient, stable and easy to industrially produce.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524801A_ABST
    Figure CN119524801A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a metal-nitrogen element co-doped carbon material by utilizing a waste artificial board and application of the metal-nitrogen element co-doped carbon material, and belongs to the technical field of artificial board waste treatment. According to the invention, the waste artificial board is used as a precursor, and metal elements and nitrogen atoms in the artificial board adhesive are introduced to be anchored in the precursor through coordination, so that the dispersibility and catalytic performance of metal active sites in a carbon skeleton are improved, and the artificial board can be used as a metal-nitrogen element co-doped carbon material. The used raw materials are waste resources, the preparation process is simple, and the obtained metal-nitrogen co-doped carbon material is large in specific surface area, excellent in catalytic activity and reusable, is a bio-based functional material with excellent performance, and can be used in the fields of pollutant adsorption in a water body environment, industrial catalysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of artificial board waste treatment, and more specifically, relates to a method for preparing a metal-nitrogen co-doped carbon material by using waste artificial boards and its application. Background Art

[0002] my country is a major country in the wood-based panel industry, and its output of wood-based panels ranks first in the world. With the rapid development of urbanization and industrialization, the service life of wood-based panel products has gradually shortened, resulting in a large number of discarded wood-based panels and related products. At present, only a few discarded wood-based panels are recycled, and most of them are directly disposed of by landfill and incineration. Traditional treatment methods cause a large amount of resource waste and impose a serious burden on the ecological environment. Therefore, it is urgent to develop low-pollution, high-efficiency, and high-value utilization and treatment technologies for wood-based panel waste.

[0003] Artificial boards are mainly composed of forest fiber and 5% to 20% resin adhesive. Forest fiber is the main component, which has a high carbon content and is a high-quality carbon precursor. At the same time, most adhesives have nitrogen-containing atomic functional groups. Therefore, after activation and carbonization of discarded artificial boards, nitrogen-rich porous carbon materials can be obtained, which can be used in the fields of adsorption and catalysis.

[0004] At present, a large amount of urban domestic wastewater and industrial and agricultural wastewater is discharged into the water, and the problem of water pollution is becoming increasingly prominent. The adsorption and catalytic degradation of pollutants by persulfate based on carbon materials is a research hotspot in the field of water purification. Most carbon materials come from non-renewable fossil resources, facing problems such as high cost, and the catalytic performance of carbon materials still needs to be improved. The introduction of metal units can be distributed and embedded on the carbon surface or empty pore channels. The generated metal active sites can improve the electron transfer rate and selectivity in the catalytic process, but direct incorporation has problems such as easy precipitation of metal ions and uneven distribution of catalytic sites. Therefore, the metal-nitrogen co-doped carbon material obtained by carbonizing metal-loaded waste artificial boards using the coordination of metal atoms and nitrogen atoms is a promising adsorption and catalytic material that can be used to adsorb and degrade pollutants in wastewater.

[0005] Chinese patent CN109626371A discloses a method for preparing N-rich activated carbon materials using waste artificial boards. The method adopts a low-temperature baking-medium-temperature carbonization-high-temperature activation method, combined with premixing and impregnation steps, to achieve the stabilization and enrichment of fuel N in the process of waste artificial boards to activated carbon. However, the N content in the waste artificial boards is limited.

[0006] Chinese patent CN117163944A discloses a preparation method and application of iron-nitrogen co-doped biochar based on waste artificial boards, using waste artificial boards as raw materials, washing, crushing and screening, and then pyrolyzing to obtain nitrogen-doped biochar; after fully mixing the nitrogen-doped biochar with ferric chloride hexahydrate and sodium bicarbonate, the activated and magnetized treatment is carried out in a vacuum tube furnace to obtain iron-nitrogen co-doped biochar. However, the two carbonizations increase the heat treatment time and energy consumption, and in the multi-step treatment process, the material will suffer from problems such as loss and unstable performance. Summary of the invention

[0007] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing metal-nitrogen co-doped carbon materials using waste artificial boards, using waste artificial boards as raw materials, undergoing coordination reaction with metal units, and high-temperature activation-carbonization to obtain metal-nitrogen co-doped carbon materials, the preparation process is simple, and it is conducive to large-scale industrial production; the first technical problem to be solved by the present invention is to provide a metal-nitrogen co-doped carbon material prepared by the above method. Another technical problem to be solved by the present invention is to provide the application of the above metal-nitrogen co-doped carbon material in the adsorption and catalytic degradation of organic pollutants in water bodies, which provides a new idea for the high-value utilization of waste artificial board resources.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a metal-nitrogen co-doped carbon material using waste artificial boards, comprising the steps of subjecting the waste artificial boards and metal units to a coordination reaction, and subjecting the waste artificial boards to high-temperature activation and carbonization to obtain the metal-nitrogen co-doped carbon material; wherein the metal doping amount in the metal-nitrogen co-doped carbon material is 0.1-5%, and the nitrogen doping amount is 1-10%.

[0010] Preferably, the waste artificial board is a plywood bonded with any one or more of urea-formaldehyde resin, melamine-formaldehyde resin, soybean-based bioadhesive, phenolic resin, epoxy resin, and polyurethane.

[0011] The method for preparing metal-nitrogen co-doped carbon material using waste artificial boards specifically comprises the following steps:

[0012] 1) crushing, screening and drying the waste artificial board to obtain waste artificial board particles;

[0013] 2) adding the waste wood-based panel particles obtained in step 1) into the metal salt solution, stirring sufficiently to obtain a mixed solution, placing the mixed solution in a high-pressure reactor for hydrothermal reaction, and filtering and drying to obtain a solid product;

[0014] 3) blending the solid product of step 2) with an activator to obtain a carbon material precursor;

[0015] 4) The carbon material precursor obtained in step 3) is placed in a high-temperature furnace protected by an inert gas for carbonization, and the carbon material is taken out after cooling, washed to neutrality, and dried to obtain a metal-nitrogen co-doped carbon material.

[0016] Preferably, in step 2), the metal salt is selected from any one or more of iron salts, cobalt salts, manganese salts, copper salts, and nickel salts. More preferably, the metal salt solution is selected from any one of ferric chloride aqueous solution, cobalt nitrate aqueous solution, and cupric chloride aqueous solution.

[0017] Preferably, in step 2), the hydrothermal reaction temperature is 150-200° C., and the hydrothermal reaction time is 8-12 h.

[0018] Preferably, in step 3), the mass ratio of the solid product to the activator is 1:1 to 2. More preferably, the mass ratio of the solid product to the activator is 1:2.

[0019] Preferably, in step 3), the activator is selected from any one of potassium hydroxide, potassium bicarbonate, sodium hydroxide, sodium bicarbonate and phosphoric acid.

[0020] Preferably, in step 3), the inert gas is nitrogen, argon or helium.

[0021] Preferably, in step 3), the carbonization temperature is 800-1000° C., and the carbonization time is 1-4 hours.

[0022] Preferably, in step 4), the solution used for washing is any one or more of dilute hydrochloric acid, water or industrial alcohol.

[0023] The method for preparing metal-nitrogen co-doped carbon material by using waste artificial boards can prepare metal-nitrogen co-doped carbon material.

[0024] The metal-nitrogen co-doped carbon material is used as an adsorbent in treating organic wastewater.

[0025] The metal-nitrogen co-doped carbon material is used as an adsorbent in treating organic wastewater, and the metal-nitrogen co-doped carbon material is added to the organic wastewater for adsorption; the amount of the metal-nitrogen co-doped carbon material is 0.05-0.15 g / L, and the concentration of organic pollutants in the organic wastewater is 10-100 mg / L.

[0026] The metal-nitrogen co-doped carbon material is used as a catalyst in treating organic wastewater.

[0027] The metal-nitrogen co-doped carbon material is used as a catalyst in treating organic wastewater, and the metal-nitrogen co-doped carbon material and persulfate are added to the organic wastewater to carry out a degradation reaction; wherein the addition amount of the metal-nitrogen co-doped carbon material is 0.05-0.15 g / L, the addition amount of the persulfate is 100 mg / L, and the concentration of organic pollutants in the organic wastewater is 10-100 mg / L.

[0028] The persulfate is peroxymonosulfate or peroxydisulfate.

[0029] The organic pollutants in the organic wastewater are any one or more of tetracycline, bisphenol A, nitenpyram, sulfamethoxazole, and ofloxacin.

[0030] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0031] 1) The artificial board used in the present invention is derived from waste such as building demolition, scrapped furniture and packaging materials, which can effectively avoid the environmental pollution and resource waste caused by the traditional method of treating waste artificial boards, and can also prepare environmentally functional bio-based carbon materials, which can be used in the fields of pollutant adsorption in water environments and industrial catalysis;

[0032] (2) The present invention provides a method for preparing metal-nitrogen co-doped carbon materials using waste artificial boards. The preparation process is simple, the equipment requirements are low, and industrial production is easy to achieve;

[0033] (3) The present invention uses waste artificial boards as precursors, and introduces metal elements and nitrogen atoms in artificial board adhesives to be anchored in the precursors through coordination, which is beneficial to effectively anchor metals during the formation of carbon materials, improves the dispersibility and catalytic performance of metal active sites in the carbon skeleton, and can effectively solve problems such as metal precipitation;

[0034] (4) The metal-nitrogen co-doped carbon material prepared by the present invention has the advantages of strong adsorption performance, excellent catalytic performance and recycling, and can be applied to the fields of pollutant adsorption and catalysis in aquatic environments, achieving waste treatment with waste, which is of great significance to sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a scanning electron microscope image of the iron-nitrogen co-doped carbon material of Example 1;

[0036] Figure 2 This is an X-ray photoelectron spectrum of carbon element in the iron-nitrogen co-doped carbon material of Example 1;

[0037] Figure 3 This is an X-ray photoelectron spectrum of nitrogen in the iron-nitrogen co-doped carbon material of Example 1;

[0038] Figure 4 This is the X-ray photoelectron spectrum of the iron element in the iron-nitrogen co-doped carbon material of Example 1. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0040] Example 1

[0041] A method for preparing a metal-nitrogen co-doped carbon material using waste artificial boards comprises the following steps:

[0042] 1) crushing, sieving and drying the waste artificial board (the amount of soybean protein-based adhesive added is 15%) to obtain 40-mesh waste artificial board particles, and the nitrogen content is 1.7% as determined by organic element analysis;

[0043] 2) 10 g of waste wood-based panel particles and 150 mL of 0.1 M ferric chloride aqueous solution were mixed, and the mixed solution was transferred to a high-pressure reactor, and the reactor was heated to 160° C. and the reaction was maintained for 12 hours to ensure that the iron ions and nitrogen ligands fully coordinated. After the reaction was completed, the mixture was filtered and placed in a drying oven at 105° C. to dry to constant weight to obtain a solid product;

[0044] 3) Weighing 10 g of the solid product dried in step 2) and 10 g of potassium hydroxide, grinding and blending, to obtain a carbon material precursor;

[0045] 4) Place 20 g of the carbon material precursor obtained in step 3) in a tubular furnace, heat it to 800 ° C at a heating rate of 10 ° C / min in a nitrogen environment, and keep it warm for 120 minutes. After naturally cooling to room temperature, take out the carbon material, rinse it with 0.4 mol / L dilute hydrochloric acid three times and then repeatedly wash it with deionized water until it is neutral. After drying, 0.98 g of iron-nitrogen co-doped carbon material is obtained.

[0046] Depend on Figure 1 It can be seen that the iron-nitrogen co-doped carbon material prepared in Example 1 is in the form of solid particles with uniform pore morphology. The specific surface area of ​​the material obtained by the fully automatic specific surface area and pore analyzer is 1631.3 m 2 / g, and the average pore size is 8.7nm.

[0047] Depend on Figures 2 to 4It can be seen that characteristic peaks of Fe (Fe 2p) and N (N 1s) elements appear at 712.80 eV and 400.90 eV, indicating that nitrogen and iron elements have been doped into the carbon grid of the carbon material. The nitrogen doping amount is 1.5% and the iron doping amount is 0.26%. The present invention successfully prepares iron-nitrogen co-doped carbon material.

[0048] Example 2

[0049] A method for preparing a metal-nitrogen co-doped carbon material using waste artificial boards comprises the following steps:

[0050] 1) crushing, sieving and drying the waste artificial board (the amount of soybean protein adhesive added was 15%) to obtain 40-mesh waste artificial board particles, and the nitrogen content was 1.7% as determined by organic element analysis;

[0051] 2) 10 g of waste wood-based panel particles and 150 mL of 0.1 M cobalt nitrate aqueous solution were mixed, and the mixed solution was transferred to a high-pressure reactor, and the reactor was heated to 180° C. and the reaction was maintained for 12 hours to ensure that the cobalt ions and the nitrogen ligands fully reacted with each other. After the reaction was completed, the mixture was filtered and placed in a drying oven at 105° C. to dry to constant weight to obtain a solid product;

[0052] 3) Weighing 10 g of the solid product dried in step 2) and 10 g of potassium hydroxide, grinding and blending, to obtain a carbon material precursor;

[0053] 4) Place 20 g of the carbon material precursor obtained in step 3) in a tubular furnace, heat it to 800 ° C at a heating rate of 10 ° C / min in a nitrogen environment, and keep it warm for 120 minutes. After naturally cooling to room temperature, take out the carbon material, rinse it with 0.4 mol / L dilute hydrochloric acid three times and then repeatedly wash it with deionized water until it is neutral. After drying, 0.86 g of cobalt-nitrogen co-doped carbon material is obtained.

[0054] Example 3

[0055] A method for preparing a metal-nitrogen co-doped carbon material using waste artificial boards comprises the following steps:

[0056] 1) crushing, sieving and drying the waste artificial board (the amount of soybean protein adhesive added was 15%) to obtain 40-mesh waste artificial board particles, and the nitrogen content was 1.7% as determined by organic element analysis;

[0057] 2) 10 g of waste wood-based panel particles and 150 mL of 0.1 M copper chloride solution were mixed, and the mixed solution was transferred to a high-pressure reactor, and the reactor was heated to 190° C. and the reaction was maintained for 12 hours to ensure that the copper ions and nitrogen ligands fully coordinated. After the reaction was completed, the mixture was filtered and placed in a drying oven at 105° C. to dry to constant weight to obtain a solid product;

[0058] 3) Weighing 10 g of the solid product dried in step 2) and 10 g of potassium bicarbonate, grinding and blending, to obtain a carbon material precursor;

[0059] 4) Place 20 g of the carbon material precursor obtained in step 3) in a tubular furnace, heat it to 1000 ° C at a heating rate of 10 ° C / min in a nitrogen environment, and keep it warm for 120 minutes. After naturally cooling to room temperature, take out the carbon material, rinse it with 0.4 mol / L dilute hydrochloric acid three times and then repeatedly wash it with deionized water until it is neutral. After drying, 0.88 g of copper-nitrogen co-doped carbon material is obtained.

[0060] Example 4

[0061] A method for preparing a metal-nitrogen co-doped carbon material using waste artificial boards comprises the following steps:

[0062] 1) crushing, sieving and drying the waste artificial board (with urea-formaldehyde resin adhesive added in an amount of 15%) to obtain 40-mesh waste artificial board particles, and determining the nitrogen content of the particles through organic element analysis to be 5.2%;

[0063] 2) 10 g of waste wood-based panel particles and 150 mL of 0.5 M ferric chloride aqueous solution were mixed, and the mixed solution was transferred to a high-pressure reactor, and the reactor was heated to 160° C. and the reaction was maintained for 12 hours to ensure that the iron ions and nitrogen ligands fully reacted with each other. After the reaction was completed, the mixture was filtered and placed in a drying oven at 105° C. to dry to constant weight to obtain a solid product;

[0064] 3) Weighing 10 g of the solid product dried in step 2) and 10 g of potassium hydroxide, grinding and blending, to obtain a carbon material precursor;

[0065] 4) Place 20 g of the carbon material precursor obtained in step 3) in a tubular furnace, heat it to 800 ° C at a heating rate of 10 ° C / min in a nitrogen environment, and keep it warm for 120 minutes. After naturally cooling to room temperature, take out the carbon material, rinse it with 0.4 mol / L dilute hydrochloric acid three times and then repeatedly wash it with deionized water until it is neutral. After drying, 0.95 g of iron-nitrogen co-doped carbon material is obtained.

[0066] Example 5

[0067] A method for preparing a metal-nitrogen co-doped carbon material using waste artificial boards comprises the following steps:

[0068] 1) crushing, sieving and drying the waste artificial board (melamine formaldehyde resin adhesive added in an amount of 15%) to obtain 40-mesh waste artificial board particles, and determining the nitrogen content of the particles through organic element analysis to be 6.3%;

[0069] 2) 10 g of waste wood-based panel particles and 150 mL of 0.5 M ferric chloride aqueous solution were mixed, and the mixed solution was transferred to a high-pressure reactor, and the reactor was heated to 160° C. and the reaction was maintained for 12 hours to ensure that the iron ions and nitrogen ligands fully reacted with each other. After the reaction was completed, the mixture was filtered and placed in a drying oven at 105° C. to dry to constant weight to obtain a solid product;

[0070] 3) Weighing 10 g of the solid product dried in step 2) and 20 g of potassium hydroxide, grinding and blending, to obtain a carbon material precursor;

[0071] 4) Place 30 g of the carbon material precursor obtained in step 3) in a tubular furnace, heat it to 800 ° C at a heating rate of 10 ° C / min in a nitrogen environment, and keep it warm for 120 minutes. After naturally cooling to room temperature, take out the carbon material, rinse it with 0.4 mol / L dilute hydrochloric acid three times and then repeatedly wash it with deionized water until it is neutral. After drying, 0.79 g of iron-nitrogen co-doped carbon material is obtained.

[0072] Comparative Example 1

[0073] 1) crushing, sieving and drying the waste artificial board (the amount of soybean protein adhesive added is 15%) to obtain 40-mesh waste artificial board particles, and the nitrogen content is 1.7% as determined by organic element analysis;

[0074] 2) Grinding and blending 10 g of waste artificial board particles, 0.2 g of ferric chloride hexahydrate and 10 g of potassium hydroxide to obtain a carbon material precursor;

[0075] 3) The carbon material precursor obtained in step 2) was placed in a tubular furnace, heated to 800°C at a heating rate of 10°C / min in a nitrogen environment, and kept warm for 120 minutes. After naturally cooling to room temperature, the carbon material was taken out, rinsed three times with 0.4 mol / L dilute hydrochloric acid, and then repeatedly washed with deionized water until neutral. After drying, 0.93 g of iron-nitrogen co-doped carbon material was obtained.

[0076] Comparative Example 2

[0077] 1) crushing, sieving and drying the waste artificial board (melamine formaldehyde resin adhesive added in an amount of 15%) to obtain 40-mesh waste artificial board particles, and determining the nitrogen content of the particles through organic element analysis to be 6.3%;

[0078] 2) 10 g of waste wood-based panel particles and 150 mL of 0.5 M ferric chloride aqueous solution were mixed, and the mixed solution was transferred to a high-pressure reactor, and the reactor was heated to 160° C. and the reaction was maintained for 12 hours to ensure that the iron ions and nitrogen ligands fully reacted with each other. After the reaction was completed, the mixture was filtered and placed in a drying oven at 105° C. to dry to constant weight to obtain a solid product;

[0079] 3) Weighing 10 g of the solid product dried in step 2) and 10 g of potassium hydroxide, grinding and blending, to obtain a carbon material precursor;

[0080] 4) Place 20 g of the carbon material precursor obtained in step 3) in a tubular furnace, heat it to 800 ° C at a heating rate of 10 ° C / min in a nitrogen environment, and keep it warm for 120 minutes. After naturally cooling to room temperature, take out the carbon material, rinse it with 0.4 mol / L dilute hydrochloric acid three times and then repeatedly wash it with deionized water until it is neutral. After drying, 0.89 g of iron-nitrogen co-doped carbon material is obtained.

[0081] Example 6

[0082] The carbon materials prepared in Examples 1-5 and Comparative Examples 1-2 (used in an amount of 0.15 g / L) were used as adsorbents. A 250 mL conical flask was used as a reactor, 100 mL of bisphenol A solution (concentration of 20 mg / L) was added, and the above carbon materials were added respectively. The reactor was placed in a shaking table at 200 rpm, and adsorption reaction was carried out at room temperature. Fixed-point sampling and analysis were performed, and the results are shown in Table 1:

[0083] Table 1 Removal rate of carbon materials prepared in Examples 1-5 and Comparative Examples 1-2 as adsorbents

[0084]

[0085] As can be seen from Table 1, the metal-nitrogen doped carbon materials prepared in Examples 1-5 and Comparative Example 2 can remove more than 90% of bisphenol A within 70 minutes when used as adsorbents. Due to the different amounts of activator added, the adsorption performance of the carbon material prepared in Comparative Example 2 is slightly lower than that of Example 5. The adsorption rate in Comparative Example 1 is relatively slow. This shows that the iron-nitrogen co-doped carbon material prepared by hydrothermal reaction using waste artificial boards as biomass raw materials has better adsorption performance.

[0086] Example 7

[0087] The carbon material prepared in Example 5 (using amount of 0.15 g / L) was used as an adsorbent. A 250 mL conical flask was used as a reactor, 100 mL of Cr (VI) solution (concentration of 100 mg / L) and the above adsorbent were added, the reactor was placed in a shaking table at 200 rpm, and the adsorption reaction was carried out at room temperature. The results of fixed-point sampling and analysis showed that the adsorption amount of Cr (VI) could reach 203.69 mg / g at 5 min and 412.32 mg / g at 70 min.

[0088] Example 8

[0089] The carbon materials prepared in Examples 1-5 and Comparative Examples 1-2 (used in an amount of 0.1 g / L) were used as catalysts. A 250 mL conical flask was used as a reactor, 100 mL of tetracycline solution (concentration of 20 mg / L), 10 mg of persulfate, and the above carbon materials were added, the reactor was placed in a shaking table at 200 rpm, the catalytic reaction was carried out at room temperature, sampling and analysis were performed, and the cycle experiment was performed. The results are shown in Tables 2 and 3:

[0090] Table 2 Removal rate of carbon materials prepared in Examples 1-5 and Comparative Examples 1-2 as catalysts

[0091]

[0092] Table 3 Removal rate of carbon materials prepared in Examples 1-5 and Comparative Examples 1-2 after 4 cycles of use

[0093]

[0094] It can be seen from Tables 2 and 3 that when the carbon materials prepared in Examples 1-5 and Comparative Example 2 are used as catalysts, more than 90% of tetracycline can be degraded within 70 minutes, and after 4 cycles of use, a removal rate of more than 50% can still be achieved. Due to the different amounts of activator added, the catalytic and cyclic performance of the carbon material prepared in Comparative Example 2 is slightly lower than that of Example 5. In Comparative Example 1, the iron element is easily precipitated, resulting in poor cyclic performance. It shows that the iron-nitrogen co-doped carbon material prepared by hydrothermal reaction using waste artificial boards as biomass raw materials has more excellent stable catalytic performance.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing metal-nitrogen co-doped carbon materials using waste artificial boards, characterized in that: The waste artificial board and the metal unit are subjected to coordination reaction, and then activated and carbonized at high temperature to obtain a metal-nitrogen co-doped carbon material; wherein the metal doping amount in the metal-nitrogen co-doped carbon material is 0.1-5%, and the nitrogen doping amount is 1-10%.

2. The method for preparing metal-nitrogen co-doped carbon material using waste artificial boards according to claim 1, characterized in that: The waste artificial board is a plywood bonded with any one or more of urea-formaldehyde resin, melamine-formaldehyde resin, soybean-based biological adhesive, phenolic resin, epoxy resin and polyurethane.

3. The method for preparing metal-nitrogen co-doped carbon material using waste artificial boards according to claim 1, characterized in that: The specific steps include: 1) crushing, screening and drying the waste artificial board to obtain waste artificial board particles; 2) adding the waste wood-based panel particles obtained in step 1) into the metal salt solution, stirring sufficiently to obtain a mixed solution, placing the mixed solution in a high-pressure reactor for hydrothermal reaction, and filtering and drying to obtain a solid product; 3) blending the solid product of step 2) with an activator to obtain a carbon material precursor; 4) The carbon material precursor obtained in step 3) is placed in a high-temperature furnace protected by an inert gas for carbonization, and the carbon material is taken out after cooling, washed to neutrality, and dried to obtain a metal-nitrogen co-doped carbon material.

4. The method for preparing metal-nitrogen co-doped carbon material using waste artificial boards according to claim 3, characterized in that: In the step 2), the metal salt is selected from any one or more of iron salts, cobalt salts, manganese salts, copper salts and nickel salts.

5. The method for preparing metal-nitrogen co-doped carbon material using waste artificial boards according to claim 3, characterized in that: In the step 2), the hydrothermal reaction temperature is 150-200° C., and the hydrothermal reaction time is 8-12 hours.

6. The method for preparing metal-nitrogen co-doped carbon material using waste artificial boards according to claim 3, characterized in that: In the step 3), the carbonization temperature is 800-1000° C., and the carbonization time is 1-4 hours.

7. The method for preparing metal-nitrogen co-doped carbon material by using waste artificial boards as described in any one of claims 1 to 6, wherein the metal-nitrogen co-doped carbon material is prepared.

8. Use of the metal-nitrogen co-doped carbon material according to claim 7 as an adsorbent in treating organic wastewater.

9. Use of the metal-nitrogen co-doped carbon material according to claim 7 as a catalyst in treating organic wastewater.

10. The use according to claim 9, characterized in that: Metal-nitrogen co-doped carbon material and persulfate are added to organic wastewater for degradation reaction; wherein, the addition amount of metal-nitrogen co-doped carbon material is 0.05-0.15 g / L, the addition amount of persulfate is 100 mg / L, and the concentration of organic pollutants in the organic wastewater is 10-100 mg / L.

Citation Information

Patent Citations

  • Method for preparing N-rich activated carbon material by utilizing waste artificial board

    CN109626371A

  • Preparation method and application of iron-nitrogen co-doped biochar based on waste artificial boards

    CN117163944A